2013
DOI: 10.1016/j.taap.2013.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur mustard induces an endoplasmic reticulum stress response in the mouse ear vesicant model

Abstract: The endoplasmic reticulum (ER) stress response is a cell survival pathway upregulated when cells are under severe stress. Severely damaged mouse ear skin exposed to the vesicant, sulfur mustard (bis-2-chloroethyl sulfide, SM), resulted in increased expression of ER chaperone proteins that accompany misfolded and incorrectly made proteins targeted for degradation. Time course studies with SM using the mouse ear vesicant model (MEVM) showed progressive histopathologic changes including edema, separation of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 53 publications
1
12
1
Order By: Relevance
“…This is concordant with our results demonstrating an association between the highest mRNA levels of Lamc2 at day 3 with a fine regenerating epidermis at day 7 for the SM dose of 0.6 mg/kg. Although the two highest doses of SM also induce an increase of Lamc2 mRNA levels in our study, the observed delay in wound repair would be explained by a lack of laminin-g2 secretion as a consequence of an endoplasmic reticulum stress related to a more severe SM-induced injury (Chang et al, 2013).…”
Section: Discussioncontrasting
confidence: 57%
“…This is concordant with our results demonstrating an association between the highest mRNA levels of Lamc2 at day 3 with a fine regenerating epidermis at day 7 for the SM dose of 0.6 mg/kg. Although the two highest doses of SM also induce an increase of Lamc2 mRNA levels in our study, the observed delay in wound repair would be explained by a lack of laminin-g2 secretion as a consequence of an endoplasmic reticulum stress related to a more severe SM-induced injury (Chang et al, 2013).…”
Section: Discussioncontrasting
confidence: 57%
“…ER stress serves as a warning mechanism against many organic environmental pollutants, and is usually indicated by up-regulation of Bip and CHOP (Chang et al, 2013;Faria et al, 2009). Previous studies have reported that 2,4-DCP affected aromatic amino acid biosynthesis (Yadav et al, 2011) and directly bound to proteins, to interfere with their conformation (Zhang et al, 2011), suggesting that 2,4-DCP may have a proteotoxicity that causes ER stress (Gardner et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of UPR is dependent on GRP78/BiP and increases in this protein are indicative of ER stress. If these ER stress survival pathways are insufficient to relieve ER stress, then the ER stress-induced apoptosis pathway involving molecules such as CHOP and caspase should be activated [37]. Moreover, Luo et al [38] reported that HMGB1 might trigger ER stress via the RAGE pathway in HMGB1 induced inflammatory endothelial cells.…”
Section: Discussionmentioning
confidence: 99%